Prevalence of Hepatitis ’C’ in Apparently Suspected Individuals of Southern Punjab by Highly Sensitive Chemiluminescence Immunoassay - SARDAR MUHAMMAD AL-FAREED ZAFAR, ASGHAR JAVAID (Journal of Fatima Jinnah Medical University, 2018)
Background: The prevalence of hepatitis C virus (HCV) infection is increasing worldwide .Hepatitis C virus (HCV) infections accounts for substantial proportions of the world wide liver disease. This study was aimed to assess the prevalence of Anti-HCV among suspected patients for hepatitis by community doctors attending collection centers of Aga Khan University Hospital's clinical laboratory Karachi in Southern Punjab. Place and Duration: A retrospective study was conducted from January 2011 to June 2011 at Multan Stat Laboratory of Aga Khan University Hospital. Methods: A total of 3341 suspected patients were received at collection centers and included in this study. The screening was performed by using the Elecsys Anti-HCV II assay kit on Cobas e 411 immunoassay analyzer. Data were entered and analyzed using SPSS version 16 statistical package. Results: From the total of 3341 suspected hepatitis patients, 2045 (61.20%) were males and 1296 (38.80%) were females. Anti-HCV was found reactive in 1002 (29.99%) borderline 20 (0.59%) and nonreactive in 2319 (69.42%). Out of the total individuals, 589 (17.63%) males and 413 (12.36%) females were Anti-HCV reactive. . . The overall seroprevalence was found to be 29.99%. LODHRAN (70%), VEHARI (49.55%), KHANEWAL (44%) and BAHAWALNAGER (37.7%) are most affected districts for HCV infection.